UJI AKTIVITAS BUAH OKRA(Abelmoschus esculentus L) TERHADAP PENURUNAN KADAR GLUKOSA DARAH PADA TIKUS - Dicky Yuswardi Wiratma; Kesaktian Manurung; Soraya Syaviera (Jurnal Farmanesia, 2020)
Diabetes mellitus is a metabolic disorder disease characterized by hyperglycemia. Abelmuschus esculentus or known as the okra plant, is often used as a treatment for DM because it has hypoglycemic and antioxidant effects. Okra (Abelmuschus esculentus) is believed by the public as one of the plants that can prevent and treat diabetes. This study aims to test whether the administration of okra fruit extract can reduce blood glucose levels in rats. The research subjects were 25 rats which were divided into 5 groups, which consisted of a negative control group with 1% NaCMC, a positive control group using glibenclamide and ethanol extract of okra fruit at a dose of 200 mg/kgBW, a dose of 250 mg/kgBW, a dose of 300 mg. /kgBB. Glucose levels were measured at T0, T1, T2, T3, T4 AND T5 using a test strip glucometer. This study was experimental.